The relationship between spiritual well-being and reflective ability: a descriptive study on intensive care nurses - Akbas, Ebru; Unlugedik, Melek (Journal of the Pakistan Medical Association, 2026)
Objective: To determine the relationship between spiritual wellbeing and reflective ability of intensive care nurses. Method: The cross-sectional, analytical study was conducted from December 2022 to April 2023 after approval from the ethics review committee of Istanbul Health Sciences University, Kanuni Sultan Suleyman Training and Research Hospital, Istanbul, Turkiye, and comprised intensive care nurses. Data was collected online using the participant information form, the Turkish version of Groningen Reflection Ability Scale, and the Spiritual Wellbeing Scale. Data was analysed using SPSS 25. Results: Of the 196 nurses, 115(58.7%) were females, 79(40.3%) were aged 22-27 years, 106(54.1%) were, 159(81.1%) possessed a university degree, 86(43.9%) had a professional experience of 1-5 years, and 124(63.3%) had 1-5 years of experience specifically in intensive care. A significant correlation was observed between the professional experience and level of spiritual wellbeing (p<0.05). The reflective ability level among female nurses surpassed that of their male counterparts (p=0.015). The mean spiritual wellbeing score was 114.23±11.08, and the mean reflection ability score was 75.27±8.23. A positive correlation existed between nurses’ spiritual wellbeing and their reflective abilities (p<0.05). Conclusions: Nurses in intensive care units exhibited an elevated degree of spiritual wellbeing and reflective ability. Nurses with higher professional seniority tended to have lower spiritual wellbeing, and male nurses tended to have lower reflective ability. Key Words: Spiritual wellbeing, Intensive care nurses, Intensive care units, Reflective ability.